Konsep Al-Musāwāh dalam Al-Qur’an: Interpretasi Hermeneutika Jorge J.E. Gracia - Lailatul Munawaroh; Muhammad Irsad; Eka Prasetiawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This article examines the concept of al-musāwāh in the Qur'an, which is one of the principles of equality emphasizing social justice universally. This study attempts to analyze the historical aspects, meanings, and implications of applying the concept of al-musāwāh in the contemporary era. The research employs a qualitative approach, utilizing primary data from the Qur'an and secondary data from relevant scientific literature reviews. The results of document analysis and a descriptive-analytical interpretive method indicate that the majority of society still shows intolerance towards differences that are inevitable. The data analysis technique employs three functions of Gracia's interpretation, highlighting forms of violence and oppression that are the root of the proliferation of discrimination and superiority cases. The research findings indicate that the application of the al-musāwāh concept in pluralistic societies still faces various obstacles due to misinterpretation of verses and the theories that exist.